APAKAH KARAKTERISTIK INDIVIDU DAN BEBAN FINANSIAL BERKONTRIBUSI PADA MASALAH KESEHATAN? BUKTI DARI INDONESIA - Manalu, Gibson; Adi, Sri Utami; Sayidah, Nur (Jurnal Manajemen dan Bisnis, 2024)
Coronary Heart Disease (CHD) poses a significant health concern in West Java, Indonesia, necessitating earnest attention in terms of prevention and management strategies. In this study, we conducted a comprehensive analysis of 300 CHD patients in West Java to identify factors contributing to the prevalence of this condition. Our findings reveal that several factors exert a notable influence on CHD prevalence in this region. Primarily, accommodation costs have been identified as a major risk factor, with an increase in housing expenses correlating positively with a rise in CHD cases. This indicates that financial hardships, particularly related to housing, can have a profound impact on cardiovascular health in West Java. Additionally, income level plays a significant role, with individuals earning higher incomes tending to have an elevated risk of CHD. Age is also a crucial factor, with older individuals exhibiting a higher propensity for CHD. Smoking habits have emerged as a significant risk factor as well. These results underscore the need for targeted attention towards economic issues and lifestyle factors in CHD prevention efforts in West Java. The implications point towards the necessity for policies supporting access to affordable housing, more effective anti-smoking campaigns, and heightened public awareness about the risk factors associated with CHD. With a deeper understanding of these factors, it is hoped that more efficacious measures can be implemented to alleviate the CHD burden in West Java.